EFEKTIVITAS PELAYANAN KELILING ONLINE PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TANAH DATAR - wingfi japami; Fitri Eriyanti (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
Since the enactment of the policy on the implementation of active systems, employees are required to provide direct services to the public. Online mobile service is a service activity that is carried out by the Population and Civil Registration Service of Tanah Datar District by visiting Nagari in Tanah Datar District. This activity in its implementation still encountered various problems, like in some areas there are only a few people because they do not know the requirements, service time that is not enough, inadequate service places and facilities, as well as internet network constrains. This study aims to analyze the effectiveness of online mobile services, find out the factors that influence and to find out about the efforts in which are committed in increasing the effectiveness of online mobile services. The method that is used is descriptive method with qualitative approach. The data that is used for this study are primary and secondary data, collected through interviews, observation and documentation studies. The results of the study indicate that the goals achievement in this service has not been comprehensive, it shows that the achievement of overall goals is weak and it is resulting in less effective mobile online services. Then, there are existed obstacles related to low public awareness, lack of socialization and internet network problems.